Seeking Ethics Approval in Colombia: A Health Systems Research Case Study - Rivillas, Juan Carlos; Ingabire, Marie-Gloriose (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
There is no single institution responsible for research ethics in health sciences in Colombia and there is no specific procedure for securing research ethics approval in the country. However, the Ministry of Health and Social Protection's resolution on health research provides guidance on key ethical considerations in health research and indicates which institutions in Colombia could provide ethics approval. Ethics approval has to be provided either by the researcher's institution of affiliation, the institution in which the research will be conducted, or the health authority responsible for the communities participating in the project. Despite this guidance, our experience with a health systems research project showed that the implementation and practice of research ethics vary between institutions. Attention should be given to ensuring effective implementation of the ethics approval process.